1997
DOI: 10.1152/jappl.1997.83.4.1090
|View full text |Cite
|
Sign up to set email alerts
|

Experimental murine acid aspiration injury is mediated by neutrophils and the alternative complement pathway

Abstract: Acid aspiration may result in the development of the acute respiratory distress syndrome, an event associated with significant morbidity and mortality. Although once attributed to direct distal airway injury, the pulmonary failure after acid aspiration is more complex and involves an inflammatory injury mediated by complement (C) and polymorphonuclear leukocytes. This study examines the injurious inflammatory cascades that are activated after acid aspiration. The role of neutrophils was defined by immunodeplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 23 publications
1
37
0
Order By: Relevance
“…Many individuals will have had trials of bronchodilators and inhaled steroids, and repeated blind trials may cause a delay in establishing an important diagnosis, such as upper airway obstruction or an endobronchial foreign body. Furthermore, for patients in whom aspiration is considered likely, bronchoscopy can provide additional information by measuring BAL neutrophils [17] and fat-laden macrophages [18]. It is important to note that the presence of some fat-laden macrophages in the BAL may be completely normal [19] and this is reflected in the present finding of a larger percentage of patients having fat-laden macrophages in BAL than the percentage with an abnormal pH study.…”
Section: Investigations In Preschool Wheezers S Saglani Et Almentioning
confidence: 58%
“…Many individuals will have had trials of bronchodilators and inhaled steroids, and repeated blind trials may cause a delay in establishing an important diagnosis, such as upper airway obstruction or an endobronchial foreign body. Furthermore, for patients in whom aspiration is considered likely, bronchoscopy can provide additional information by measuring BAL neutrophils [17] and fat-laden macrophages [18]. It is important to note that the presence of some fat-laden macrophages in the BAL may be completely normal [19] and this is reflected in the present finding of a larger percentage of patients having fat-laden macrophages in BAL than the percentage with an abnormal pH study.…”
Section: Investigations In Preschool Wheezers S Saglani Et Almentioning
confidence: 58%
“…Soluble CR1 also prevented the progression of disease in rat arthritis models, such as monarticular arthritis (39), CIA (40), and tumor necrosis factor (TNF)- (41) and anti-CD59-induced arthritis (42). Treatment with sCR1 in mice reduced acid aspiration injury (43), reperfusion/ ischemia injury of skeletal muscle (44), contact sensitivity and delayed-type hypersensitivity (45), and ultraviolet induction of immunosuppression (46).…”
mentioning
confidence: 99%
“…Proximal GER creates the potential for aspiration, the outcome of which varies with the chronicity of the events and the volume and nature of the aspirate. Acute pneumonitis results from aspiration of a large volume of acidic fluid [29], and animal studies have shown this to be a biphasic process [30,31]: initial chemical injury followed by an inflammatory phase [32][33][34]. Food particles and low pH act synergistically to produce a more severe injury with a different cytokine profile from that generated by acid alone [35,36].…”
Section: Mechanisms Of Respiratory Disease In Gerdmentioning
confidence: 99%